2010
DOI: 10.3329/cerb.v14i1.3940
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preservatives on extending the shelf-life of Rasogolla

Abstract: The study aims, to find out an effective preservative to extend the shelf-life of Rasogolla, a highly popular sweetmeat due to its special appeal of taste, as well as to assess the effect of preservative on its biochemical and microbial status. Rasogolla available in local market has too short shelf life (2-3days) since its processing and preservation still lack standardization. In this research, Rasogolla was prepared in laboratory using calcium propionate, sodium metabisulfite, sorbic acid, sodium diacetate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Shelf life variation of different milk products are shown in Figure 3 and it indicates that the shelf life of rasogolla, malaikari, chomchom, pedasandesh and danadarmisti was minimum 3 days and maximum 5 days. This finding was similar to Das et al (2010) who reported that the shelf life of market rasogolla's lasted for 2-3 days. The shelf life of rasomalai and kalojam were maximum 5 and minimum 2 and 4 days, respectively.…”
Section: Shelf Life Variation In Different Milk Products At Mymensingsupporting
confidence: 81%
“…Shelf life variation of different milk products are shown in Figure 3 and it indicates that the shelf life of rasogolla, malaikari, chomchom, pedasandesh and danadarmisti was minimum 3 days and maximum 5 days. This finding was similar to Das et al (2010) who reported that the shelf life of market rasogolla's lasted for 2-3 days. The shelf life of rasomalai and kalojam were maximum 5 and minimum 2 and 4 days, respectively.…”
Section: Shelf Life Variation In Different Milk Products At Mymensingsupporting
confidence: 81%
“…The use of preservatives in combination was proved to extend the maximum shelf life of Rasmalai without any taste change. In a study conducted on the shelf stability of rasgolla, it was observed that the shelf stability of rasgolla increased up to 24 days by using sorbic acid (Das et al., 2010 ). They observed improved organoleptic properties of rasgollas during storage.…”
Section: Resultsmentioning
confidence: 99%
“…and overall acceptability (e) of Rasmalai during storage (0-12 days, 5°C) using different preservatives (R 0 = Control (Rasmalai) treatment (without addition of any preservative); R 1 = Rasmalai prepared using 500 ppm potassium sorbate; R 2 = Rasmalai prepared by using 1000 ppm potassium sorbate; R 3 = Rasmalai prepared by using 500 ppm calcium propionate; R 4 = Rasmalai prepared by using 1000 ppm calcium propionate; R 5 = Rasmalai prepared using combination of both potassium sorbate and calcium propionate in equal quantity, i.e., 500 ppm each). conducted on the shelf stability of rasgolla, it was observed that the shelf stability of rasgolla increased up to 24 days by using sorbic acid (Das et al, 2010). They observed improved organoleptic properties of rasgollas during storage.…”
Section: Total Plate Counts (Tpc) and Yeast And Mold (Y And M) Of Ras...mentioning
confidence: 99%
See 1 more Smart Citation
“…Sorbic acid possesses antifungal and antimicrobial properties. Therefore, the combination of sodium metabisul te and sorbic acid kills or inhibits growth of microbes responsible for spoiling nipa palm sap [12]. A higher number of TBC was observed in the control sample as it does not have any substances that impede the growth and proliferation of bacteria which naturally occur in the nipa palm sap.…”
Section: Discussionmentioning
confidence: 95%